Rapid analysis of dechloranes in sediment and soil by selective pressurized liquid extraction using Mg–Al layered double oxides as sorbents. Issue 7 (8th February 2017) - Zhao, Tan; Tang, Hua; Chen, Dazhou; Huo, Feifei; Li, Lei
Abstract : Dechloranes are chlorinated flame retardants, including Dechlorane Plus (DP), dechlorane 602 (Dec 602), dechlorane 603 (Dec 603), dechlorane 604 (Dec 604) and Mirex. Abstract : Dechloranes are chlorinated flame retardants, including Dechlorane Plus (DP), dechlorane 602 (Dec 602), dechlorane 603 (Dec 603), dechlorane 604 (Dec 604) and Mirex. In this research, dechloranes in sediment and soil were extracted and purified by the selective pressurized liquid extraction (SPLE) method. Chromatographic separation, detection and quantification were achieved by gas chromatography-electron capture negative ionization mass spectrometry (GC-ECNI-MS). As novel and low-cost sorbents, Mg–Al layered double oxides (Mg–Al-LDOs) were selected as SPLE sorbents. SPLE parameters affecting the extraction efficiency, including extraction temperature, the type of extraction solvent, and static extraction time and cycles, were optimized in detail. Beside the optimization of instrumental parameters for SPLE, the type and amount of sorbent that may affect the cleanup effect were also investigated. Under optimal conditions, the recoveries of the dechloranes with three-spiked concentration levels (10, 100, and 500 ng g −1 ) were in the range of 90.3–99.8% with the relative standard deviation less than 5.7%. The method showed excellent linearity over the range assayed (1–500 ng g −1 ) with a determination coefficient ( R 2 ) of 0.9992–0.9999. The limits of detection (LODs) ranged from 0.01 to 0.67 ng g −1 and the limits of quantification (LOQs) were ranging from 0.03 to 2.22 ng g −1 . The analytical method developed was successfully applied for the determination of dechloranes in sediment samples collected in Shandong, China. The concentrations of Mirex, Dec 602, Dec 603, and syn - and anti -DP ranged from lower quantification limits to 1.63 ng g −1 dry weight (dw), 0.65–1.85 ng g −1 dw, 0.74 ng g −1 dw, 0.65–55.78 ng g −1 dw and 2.20–167.42 ng g −1 dw, respectively. Dec 604 was not detected in any samples. The results indicated that SPLE with Mg–Al-LDOs as clean-up sorbents is a fast and reliable extraction technique offering many advantages compared to traditional techniques.